Emergency Remote Teaching and Beyond Voices from World Language Teachers and Researchers - Chen, Julian (Springer, 2022)
This timely volume addresses issues pertaining to language teaching, learning and research during the pandemic. In times of a global emergency, the aftermath of emergency remote teaching (ERT) cannot be ignored.